A drug court by any other name? An analysis of problem-solving court programs - Kaiser, Kimberly A; Rhodes, Kirby (Law and human behavior, 2019)
Beginning with the original drug court model, specialized court programs (SCPs) have expanded to address a variety of offense-related problems, such as domestic violence courts, mental health courts, veteran courts, and homeless courts. To date, there has been no empirical assessment as to whether these types of court programs share similar program characteristics with the drug court model. To address this gap, we used data from the 2012 Census of Problem-Solving Courts of 2,793 problem-solving court programs in the United States to examine differences between drug courts and other court types. We used multinomial logistic regression to analyze program-level characteristics between SCPs and drug courts. SCPs were similar on several key characteristics to drug courts, such as specialization and services, staff training, and procedures. Where SCPs tend to differ were whether felony offenders were allowed, charges dismissed after program completion, and participants entering the program post-adjudication. Though they may go by different names, many SCPs continue to rely on the original drug court model. Future research within the drug court paradigm should consider expanding to other types of SCPs to provide more comprehensive knowledge on the "black box" of problem-solving courts and how courts can more effectively implement court programs. (PsycINFO Database Record (c) 2019 APA, all rights reserved).